Characterization of hybrid plasmids carrying individual ribosomal ribonucleic acid transcription units of Escherichia coli. - Kenerley, M E (1977)
We have screened the strains with ColE1 hybrid plasmids constructed by Clarke and Carbon (Cell 9:91-99, 1976) for the presence of ribosomal ribonucleic acid (rRNA) genes on the plasmids and identified 16 strains whose plasmids carry rRNA genes. The structures of these 16 plasmids were compared by heteroduplex analysis, and the plasmids were classified into six groups on the basis of their chromosomal origins. Homology with known transducing-phage deoxyribonucleic acids and genetic mapping have assigned locations on the Escherichia coli chromosome to three of the six groups. These are rrnB near rif at 88 min, rrnC near ilvE at 83 min, and rrnD near aroE at 71 min. A fourth group is probably rrnA at 85 min (T. Ikemura and M. Nomura, Cell, 11:779-793, 1977). We conclude that the minimum number of rRNA transcription units per haploid chromosomes is seven, that is, the six groups identified in this work plus a known operon (rrnE near metA at 89 min) that we failed to find among the hybrid plasmids. This heteroduplex analysis also suggests that there are only two kinds of rRNA operons with respect to their spacer region; three of the six rRNA operon groups studied here have one kind, whereas the remaining three have the other kind.